Valoração econômica do meio ambiente : aplicação do Método do Custo de Oportunidade em áreas impactadas pelo desmatamento no município de Rorainópolis - RR - Bispo, Lorenna Grasielle Silva (2017)
The economic valuation of the environment has been a fundamental precept for the definition of environmental policies, which are used as an instrument of environmental planning and management. The economic analysis of natural resources counts on the use of environment aluation methods, which in the specific case of this dissertation, opted for the Opportunity Cost Method, which is always used to estimate the income sacrificed in terms of economic activities, or in deforest áreas that are in desuse. It is known that in Brazil, development projects of the Federal Government have reserved ofr the Brazilian Amazon a huge environment degradation. Our object of study is the city of Rorainópolis, located in the south of the state of Roraima, is linked to this historical process of marginal erosion, and it is in this sense that the need to value deforestation in the municipality of Rorainópolis was verified. The work seeks to monetarily assess the cost os areas impacted by deforestation in thecity mentioned above, through the Opportunity the areas that are in disuse, that is, areas that are being deforested, but are not reflecting in a use of agricultural production. The calculation to find the opportunity cost of deforestation, which was R$31,073.415 million. This value demonstrates a signal for the investments that encourage production in areas of disused.